EKONOMI YANG INKLUSIF DAN BERKELANJUTAN: ANALISIS KEUANGAN DAERAH, KEMISKINAN, DAN TEKNOLOGI UNTUK MEWUJUDKAN SDGS 2030 - Herman, Nur Ashilah Raihanah; Muchtar, Masruri; Sihombing, Pardomuan Robinson (Jurnal Bayesian : Jurnal Ilmiah Statistika dan Ekonometrika, 2024)
The Sustainable Development Goals (SDGs) emerged as a universal commitment to address social issues, prioritize inclusive economic growth, and reduce inequality. Regional governments are the main pillar in achieving the 2030 SDGs in addition to other factors, namely GDP per capita and economic inclusivity by emphasizing regional equity and increasing local independence. This study analyzes the impact of regional finance, poverty, and technology on economic growth in order to realize an inclusive and sustainable economy. The data is sourced from the Central Statistics Agency and the Directorate General of Financial Balance for 2020-2022 which covers all provinces in Indonesia. Using a fixed effect model, the test results found that local income, profit-sharing funds, and technology had a positive impact on per capita economic growth, but poverty showed a negative influence. The implications of these findings show the need for a comprehensive study related to the implementation of fiscal decentralization and technology investment so that it can achieve the 8th goal of the 2030 SDGs